Spread through air spaces is a powerful prognostic predictor in patients with completely resected pathological stage I lung adenocarcinoma. (December 2022) - Shimomura, Masanori; Miyagawa-Hayashino, Aya; Omatsu, Ikoi; Asai, Yumi; Ishihara, Shunta; Okada, Satoru; Konishi, Eiichi; Teramukai, Satoshi; Inoue, Masayoshi
Highlights: 32.8% of patients underwent lung resection for pathological stage I adenocarcinoma had STAS. 42.4% of patients underwent lobectomy for pathological stage I adenocarcinoma had STAS. STAS correlated with a large consolidation size, larger invasive size. STAS was an independent predictor associated with postoperative local recurrence. STAS-positive stage IA cases had worse outcomes than STAS-negative stage IA cases. Abstract: Purpose: To evaluate the frequency of spread through air spaces (STAS) in patients with early-stage primary lung cancer and to elucidate the association between STAS and various clinicopathological factors. Methods: We retrospectively reviewed data from a total of 265 consecutive patients who underwent lobectomy and mediastinal lymph node dissection (172 patients) or sublobar resection (93 patients) for completely resected pathological stage I lung adenocarcinoma. We evaluated clinical variables, including the preoperative serum carcinoembryonic antigen (CEA) level, tumour size, consolidation tumour ratio (CTR), maximum standardized uptake value (SUVmax) on FDG-PET, histological results, presence of STAS and vascular and lymphatic invasion. Results: The median follow-up time after surgery was 49 months. Eighty-seven patients (32.8 %) had STAS. The overall survival rates of patients in the STAS-positive and STAS-negative groups were 92.7 % and 97.1 % at 3 years, respectively (p = 0.1255), and the recurrence-free survival rates were 82.1 % and 95.9 % at 3 years, respectively (p = 0.0001). STAS was found in 73 patients (42.4 %) in the lobectomy group, which was a significantly higher proportion than the 14 patients (15.1 %) in the sublobar resection group. The STAS-positive group had significantly larger areas of invasion, higher CTRs, preoperative CEA and SUVmax levels, and more lymphatic and vascular invasion. STAS also correlated significantly with large consolidation sizes, larger invasive size, higher CTRs and the presence of a micropapillary pattern. Cox regression analysis after adjustment for important prognostic factors revealed that the presence of STAS was an independent predictor associated with postoperative recurrence, most of which was observed locoregionally. Conclusions: STAS was an independent factor associated with postoperative recurrence after lung resection for stage I lung adenocarcinoma. Among stage IA patients, the postoperative outcomes of STAS-positive patients were worse than those of STAS-negative patients and were similar to those of stage IB patients.